2013
DOI: 10.1093/eurheartj/eht023
|View full text |Cite
|
Sign up to set email alerts
|

The eye and the heart

Abstract: The vasculature of the eye and the heart share several common characteristics. The easily accessible vessels of the eye are therefore—to some extent—a window to the heart. There is interplay between cardiovascular functions and risk factors and the occurrence and progression of many eye diseases. In particular, arteriovenous nipping, narrowing of retinal arteries, and the dilatation of retinal veins are important signs of increased cardiovascular risk. The pressure in the dilated veins is often markedly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
304
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 334 publications
(316 citation statements)
references
References 106 publications
7
304
0
5
Order By: Relevance
“…10c). The effect of PKI (14)(15)(16)(17)(18)(19)(20)(21)(22) (2 μM) was the same as that observed in the presence of H-89 (n = 8) (data not shown). SQ22536 (100 μM) also completely blocked this increase (n = 8) (Fig.…”
Section: + ] I Increase In Vorticose Veinssupporting
confidence: 64%
See 2 more Smart Citations
“…10c). The effect of PKI (14)(15)(16)(17)(18)(19)(20)(21)(22) (2 μM) was the same as that observed in the presence of H-89 (n = 8) (data not shown). SQ22536 (100 μM) also completely blocked this increase (n = 8) (Fig.…”
Section: + ] I Increase In Vorticose Veinssupporting
confidence: 64%
“…Sympathetic nerves from the superior cervical ganglion project to the choroid and, when stimulated, elicit marked vasoconstriction throughout the choroid (39,67). The retinal vasculature shares many anatomical and physiological features with the cerebral and coronary vasculature, which are exposed to similar intrinsic and environmental influences (17,53). Retinal vessel caliber sizes convey different information about systemic diseases, with arteriolar narrowing being associated with elevated blood pressure (10,40,81).…”
Section: Preparation Of the Ciliary Arteries And Vorticose Veinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eye as a direct window to vascular function has an appeal beyond structural assessment [54]. Static and dynamic retinal vessel analyses (RVA) are unique and elegant in several ways.…”
Section: How Can We Measure Endothelial Function?mentioning
confidence: 99%
“…1,2 Altered ocular blood flow was reported to accelerate the development and progression of the disease in such patients; as such, not only elevated IOP, but also medical conditions that negatively affect ocular blood flow will obviously cause ischemia and reperfusion damage in glaucoma patients and in individuals prone to glaucoma. [3][4][5] Hemodialysis (HD) is an important component of the treatment of end-stage renal disease (ESRD). Some studies have reported the effects of HD on IOP, but the findings are inconsistent.…”
Section: Introductionmentioning
confidence: 99%